Pengaruh Brand Experience dan Electronic Word of Mouth terhadap Brand Trust Blu by BCA Digital (Studi pada Mahasiswa di Kota Malang) - Sefira Aulia Evanda; Rizky Kurniawan Murtiyanto (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Customer trust is a crucial factor in digital banking services, particularly amidst high cybersecurity risks. This study aims to examine the effect of brand experience and electronic word of mouth (e-WOM) on brand trust among university student users of the Blu by BCA Digital application in Malang City. This study employs an explanatory quantitative method with a sample of 100 respondents selected through purposive sampling from a student population across five universities. Data was collected via an online questionnaire and analyzed using multiple linear regression with SPSS software. The results reveal that, partially, brand experience has a positive and significant effect on brand trust. Conversely, e-WOM exerts a positive but insignificant effect. Simultaneously, both variables significantly affect brand trust, with brand experience acting as the dominant factor. These findings confirm that in the digital banking context, direct user experience (app features, navigation, and service stability) is far more effective in building trust compared to reviews or recommendations from other users. The practical implication for the company is the necessity to enhance feature functionality, application stability, and customer service quality. Future research is recommended to include variables like perceived risk or e-service quality and test e-WOM as a mediating or moderating variable.